Biting rhythm and demographic attributes of Aedes albopictus (Skuse) females from different urbanized settings in Penang Island, Malaysia under uncontrolled laboratory conditions - Muhammad, Nor Atikah Farhah (PLoS One, 2020)
Urbanization could potentially modify Aedes albopictus’ ecology by changing the dynamics of the species, and affecting their breeding sites due to environmental changes, and thus contribute to dengue outbreaks. Thus, this study was conducted to evaluate the biting rhythm, fecundity and longevity of adult female Ae. albopictus in relation to urbanization strata; urban, suburban and rural areas in Penang Island, Malaysia. The experiments were done in comparison to a laboratory strain. Twenty-four hours biting activity of all the mosquito strains showed a clear bimodal biting activity, with morning and evening twilight peaks. The interaction effect between biting time and mosquito strains was not significant. Meanwhile, differences in fecundity among mosquito strains were statistically significant (F(3,442) = 10.559, P < 0.05) with urban areas having higher mean number of eggs (mean = 107.69, standard error = 3.98) than suburban (mean = 94.48, standard error = 5.18), and rural areas (mean = 72.52, standard error = 3.87). Longevity of adult females were significantly higher (F(3,441) = 31.259, P < 0.05) for mosquito strains from urban areas compared to the other strains. These findings would provide crucial information for the planning of control programs in Malaysia, particularly Penang.